De novo mutations in the X-linked TFE3 gene cause intellectual disability with pigmentary mosaicism and storage disorder-like features. Issue 12 (14th May 2020) - Lehalle, Daphné; Vabres, Pierre; Sorlin, Arthur; Bierhals, Tatjana; Avila, Magali; Carmignac, Virginie; Chevarin, Martin; Torti, Erin; Abe, Yuichi; Bartolomaeus, Tobias; Clayton-Smith, Jill; Cogné, Benjamin; et al.
Abstract : Introduction: Pigmentary mosaicism (PM) manifests by pigmentation anomalies along Blaschko's lines and represents a clue toward the molecular diagnosis of syndromic intellectual disability (ID). Together with new insights on the role for lysosomal signalling in embryonic stem cell differentiation, mutations in the X-linked transcription factor 3 ( TFE3 ) have recently been reported in five patients. Functional analysis suggested these mutations to result in ectopic nuclear gain of functions. Materials and methods: Subsequent data sharing allowed the clustering of de novo TFE3 variants identified by exome sequencing on DNA extracted from leucocytes in patients referred for syndromic ID with or without PM. Results: We describe the detailed clinical and molecular data of 17 individuals harbouring a de novo TFE3 variant, including the patients that initially allowed reporting TFE3 as a new disease-causing gene. The 12 females and 5 males presented with pigmentation anomalies on Blaschko's lines, severe ID, epilepsy, storage disorder-like features, growth retardation and recognisable facial dysmorphism. The variant was at a mosaic state in at least two male patients. All variants were missense except one splice variant. Eleven of the 13 variants were localised in exon 4, 2 in exon 3, and 3 were recurrent variants. Conclusion: This series further delineates the specific storage disorder-like phenotype with PM ascribed to de novo TFE3 mutation in exons 3 and 4. It confirms the identification of a novel X-linked human condition associated with mosaicism and dysregulation within the mechanistic target of rapamycin (mTOR) pathway, as well as a link between lysosomal signalling and human development.